Effect of the Look-back period for the estimation of the incidence rates using administrative data - Mira Kim; Kyung-Hee Chae; Chai Young Jung; Youn-Jee Chung; Minkyoung Lee; Hyun-Kyung Kim; Hye-Jin Hwang; Hyun-Hee Choi; Mee-Ran Kim; Sukil Kim (International Journal of Population Data Science, 2018)
Introduction Administrative data are widely used to estimate epidemiologic indicators. The look-back period is needed to define baseline population for the incidence. However, short look-back period is known to overestimate incidence of diseases misclassifying prevalent cases to incident cases. A short look-back period with longer observation period causes misclassification more inconsistent.